FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN IMUNISASI PENTABIO DI DESA BATANG KUIS PEKAN - Suci Nanda Resti Tarigan (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Basedon surveillance data from the Ministry of Health 2020, the situation of diphtheria in Indonesia, in2019 the number of suspected diphtheria cases was 944 casesspread across 25 provinces, while upto May 2020, there were 129 cases of suspected diphtheria found in 16 provinces. To prevent the incidence of diphtheria, the government is targeting the achievement of basic immunization coverage. The type of researchused in this research is analytic which aims to determine the factors related to the provision of Pentabio immunization in Batang Kuis Pekan Village in2020. Mothers who have babies (11-12 months) in Batang Kuis Pekan Villageare 137 people, The sampling technique in this study used simple random sampling totaling 57 people. Data analysis using Chi- square analysis. The results of the study found that there was a significant relationship between knowledge (p-value = 0.037) and family support (p-value 0.05) with the provision of Pentabio immunization in Batang Kuis Pekan Village in2020. From the results In this study, respondents should increase their knowledge that is less and better and change their behavior, respondents can increase their knowledge about immunization through health personnel facilities, orexisting books so that they want to administer pentabio immunization.